A review of lossless audio compression standards and algorithms - Abdul Muin, Fathiah; Gunawan, Teddy Surya; Kartiwi, Mira; Elsheikh, Elsheikh Mohamed Ahmed (American Institute of Physics, 2017)
Over the years, lossless audio compression has gained popularity as researchers and businesses has become more aware of the need for better quality and higher storage demand. This paper will analyse various lossless audio coding algorithm and standards that are used and available in the market focusing on Linear Predictive Coding (LPC) specifically due to its popularity and robustness in audio compression, nevertheless other prediction methods are compared to verify this. Advanced representation of LPC such as LSP decomposition techniques are also discussed within this paper.